Efficacy and Safety of a Multistrain Probiotic Formulation Depends from Manufacturing - Trinchieri, Vito; Laghi, Luca; Vitali, Beatrice; Parolin, Carola; Giusti, Ilaria; Capobianco, Daniela; Mastromarino, Paola; De Simone, Claudio (Frontiers in Immunology, 2017)
Background: Variability in probiotics manufacturing may affect their properties, with potential implications for their efficacy and safety. This is of particular concern with probiotic products destined for use in patients with serious medical conditions, including HIV infection. The purpose of the study was to carry out a series of experiments comparing the properties of the US-made probiotic formulation originally commercialized under the brand name VSL#3®, with those of the Italian-made formulation now commercialized under the same name. The US-made formulation has previously shown beneficial effects at the intestinal and neurological levels in HIV-infected subjects as well as in patients with Inflammatory Bowel Diseases (IBD) and hepatic encephalopathy. Methods: Eleven subjects receiving combined antiretroviral therapy (cART) for HIV-1 were treated for 6 months with the US-made VSL#3 formulation. At baseline and 6 months, T-cells were analyzed for phenotype and activation markers, and fecal samples were analyzed for bifidobacteria, lactobacilli and their metabolites. The fecal metabolome was assessed using 1H-NMR spectroscopy. Production of metabolites of interest by bacteria obtained from sachets of the two formulations were compared in vitro and their effects on a rat intestinal epithelial cell line (IEC-6) were assessed. Particular attention was paid to the metabolite 1,3-dihydroxyacetone (DHA). Results: At 6 months fecal samples showed a significant increase in the specific bacterial genera contained in the probiotic supplement. Immune activation was reduced as shown by a significant reduction in the percentage of CD4+CD38+HLA-DR+ T-cells at 6 months. Fecal concentrations of DHA decreased significantly. In vitro, significant differences in the production and metabolism of DHA were found between bacteria from the US-made and Italian-made formulations: the US-made formulation was able to metabolize DHA whereas the bacteria in the Italian-made formulation were producing DHA. DHA reduced the viability of Staphylococcus thermophilus, reduced IEC-6 cell viability in a dose-dependent manner, and also led to a lower rate of repair to scratched IEC-6 cell monolayer. Conclusion: Our data, in conjunction with previously published findings, confirm that the new Italian –made formulation of VSL#3® is different from the previous US-made VSL#3 and therefore its efficacy and safety in HIV-infected subjects is still unproven.